Depth an account of scientific explanation - Strevens, Michael (Harvard University Press, 2011)
"What does it mean for scientists to truly understand, rather than to merely describe, how the world works? Michael Strevens proposes a novel theory of scientific explanation and understanding that overhauls and augments the familiar causal approach to explanation. What is replaced is the test for explanatorily relevant causal information: Strevens discards the usual criterion of counterfactual dependence in favor of a criterion that turns on a process of progressive abstraction away from a fully detailed, physical causal story. The augmentations include the introduction of a new, non-causal explanatory relevance relation - entanglement - and an independent theory of the role of black-boxing and functional specification in explanation." "The result is an account of explanation that has especially significant consequences for the higher-level sciences: biology, psychology, economics, and other social sciences."--Jacket.